Molecular imaging in Parkinson's disease - Polito, Cristina (Premio Tesi di Dottorato, 2011)
The present work explores brain functional changes in drug-naïve Parkinson's disease (PD) patients by means of molecular imaging techniques. Thirty-one consecutive drug-naïve PD patients from the Neurological Clinic of the University of Flor-ence underwent clinical assessment, neuropsychological assessment, MRI, [123I]FP-CIT SPECT, [18F]FDG PET. First, [18F]FDG-PET was employed to identify in drug-naïve PD patients brain metabolic alteration uniquely related to disease process and not modulated by anti-parkinsonian therapeutic intervention. Second, [18F]FDG-PET and [123I]FP-CIT SPECT were employed together to explore the early functional changes in brain function related to dopaminergic depletion in the putamen and in the caudate nucleus.